A Meta-Analysis on Degraded Alpine Grassland Mediated by Climate Factors: Enlightenment for Ecological Restoration - Yu, Jiale; Wan, Lingfan; Liu, Guohua; Ma, Keming; Cheng, Hao; Shen, Yu; Liu, Yuqing; Su, Xukun (Frontiers in Plant Science, 2022)
Alpine grassland is the main ecosystem on the Qinghai-Tibet Plateau (QTP). Degradation and restoration of alpine grassland are related to ecosystem function and production, livelihood and well-being of local people. Although a large number of studies researching on degraded alpine grassland, there are doubts about degradation patterns of alpine grassland in different areas and widely applicable ecological restoration schemes due to the huge area of the QTP. Here, we used meta-analysis method to synthesize 80 individual published studies which were conducted to examine aboveground and underground characteristics in non-degraded (ND), lightly degradation (LD), moderately degradation (MD), heavily degradation (HD), and extremely degradation (ED) of alpine grassland on the QTP. Results showed that aboveground biomass (AGB), belowground biomass (BGB), Shannon-wiener index, soil moisture (SM), soil organic carbon (SOC), soil total nitrogen (TN) and available nitrogen (AN) gradually decreased along the degradation gradient, whereas soil bulk density (BD) and soil pH gradually increased. In spite of a tendency to soil desertification, losses of other soil nutrients and reduction of enzymes, the variations were not linear changes along the degradation gradient. Moreover, the decreasing extent of TN was smaller in areas with more precipitation and higher temperature and the decreasing extent of AGB, SOC and TN was larger in areas with higher extent of corresponding variables in the stage of ND during alpine grassland degradation. Those findings suggest that in areas with more precipitation and higher temperature, reseeding and sward cleavage can be used for restoration on degraded alpine grassland. Fencing and fertilization can be used for alpine grassland restoration in areas with less precipitation and lower temperature. Microbial enzymes should not be used to restore degraded alpine grassland in a large scale on the QTP without detailed investigation and analysis. Future studies should pay more attention to the effects of climate factors on degradation processes and specific ecological restoration strategies in different regions of QTP.